Frequency and Determinants of Spontaneous Conversion to Sinus Rhythm in Patients Presenting to the Emergency Department with Recent-onset Atrial Fibrillation: A Systematic Review. Issue 4 (2020) - Pluymaekers, Nikki AHA; Luermans, Justin GLM; Hermans, Astrid NL; Weijs, Bob; Linz, Dominik K; Vernooy, Kevin; Dudink, Elton AMP; Crijns, Harry JGM
No abstract available